Detection and typing of human papillomavirus in cervical specimens of Turkish women - (:unkn) unknown (IMR PRESS, 1997)
The DNA in situ hybridization (DISH) and conventional solution phase polymerase chain reaction (PCR) were applied to identify human papillomavirus (HPV) DNA in cervical specimens uf Turkish women. Samples consisted of 21 cervical brushings from pregnant women and 20 paraffin-embedded biopsies from women with condylomatous or dysplasic lesions. It was found that two out of 21 (9.5%) pregnant women were harbouring HPV-DNA detected by PCR. One woman was infected with HPV 16/30's and the other with an unidentified type. As for the biopsy specimens, the rate of HPV-DNA positivity was 30% and 45% by DISH and PCR, respectively. A double infection was observed In more than 50% of the positive cases, Moreover, HPV 18 was never detected. The results indicated that HPV-DNA is rarely present in cytomorphologically normal smears from pregnant women. The PCR method was successfully adapted for HPV typing in clinical Lesions which simultaneously contained different HPV sequences.
Keywords: HPV; cervix; pregnancy; dysplasia; DISH; PCR; POLYMERASE CHAIN-REACTION; INSITU HYBRIDIZATION; INTRAEPITHELIAL NEOPLASIA; GENITAL LESIONS; INFECTION; DNA; AMPLIFICATION; CARCINOMA; PCR; PREVALENCE